Oral versus intravenous clarithromycin in moderate to severe community-acquired pneumonia: an observational study. Issue 1 (December 2017) - Rae, Nikolas; Singanayagam, Aran; Schembri, Stuart; Chalmers, James
Abstract Objectives British Thoracic Society guidelines recommend clarithromycin in addition to beta-lactam antibiotics for patients with community-acquired pneumonia and CURB-65 score 2–5. Intravenous therapy is commonly used but there are few data on whether oral therapy is equally effective. Methods This observational study used propensity matching to compare two groups of patients with moderate to severe community-acquired pneumonia (CURB-65 score 2–5) treated with oral (n = 226) or intravenous (n = 226) clarithromycin on admission. Outcomes were 30-day mortality, intensive care unit admission, time to clinical stability, and length of hospital stay. Results There was no significant difference in 30-day mortality (16.8% for intravenous [IV] group vs. 14.6% for oral group, hazard ratio for IV group 1.11 95% CI 0.70–1.78), ICU admission (10.6% in both groups) or complications (10.6% for IV group and 9.3% for oral group) between the groups. The time to clinical stability in both cohorts was a median of 5 days (interquartile range 3–7 days, p = 0.3). The median length of hospital stay was 8 days in the IV group (interquartile range 4–14 days) and 7 days in the oral group (interquartile range 4–13 days), p = 0.5. No other differences were observed between oral and IV groups. Conclusion Where the oral route is not compromised, oral macrolides appear to be equivalent to IV in treating moderate to severe CAP.